Prelude Before Nobel – Enriching Learning Environment with a Knowledge Concert; Colliding Art and Science. Concept, Origin, and Purpose - Horwitz, Eva Bojner; Thyrén, David (European Journal of Applied Sciences, 2024)
The concept of the knowledge concert was developed by researchers at the Royal College of Music and Karolinska Institute in Sweden where live musicians and scientific researchers creates a performance related to an important societal issue. The emotional evocativeness music allows it to act as a facilitator of knowledge acquisition which it is argued enriches the learning environment. In this study, we have built on the idea of the knowledge concert with a novel focus on Nobel prize winners’ work. Knowledge is generated from live musicians and narratives from a cicerone. The two originators will in this study develop the concept of Prelude before Nobel as a knowledge concert. Further knowledge related to the Nobel Prize scientific findings was obtained by listening to live music. In this experience thoughts and feelings were stimulated, which increased the receptivity and understanding of the Nobel Prize in terms of both content and meaning.